Proposta para identificação rápida dos períodos hidrológicos em áreas de várzea do rio Solimões-Amazonas nas proximidades de Manaus - Bittencourt, Maria Mercedes (Acta Amazonica, 2020)
Seasonal variations of the water level is the most important factor in determining the community of aquatic organisms present in flooded areas in the Amazon. Many scientific projects developed in this region were and still are being carried out in flooded areas near the city of Manaus; however, data can rarely be compared due to a non-standardized nomenclature used to describe the various phases of the flood pulse. The present paper aims to identify and standardize the terminology used to define a hydrological cycle with the purpose of allowing for the analysis of data from different places and multiple years. Serial data of the Negro River water height taken from the local harbor was considered for the estimations. Values of the water height are proposed in order to define the four hydrological periods (rising, flood, lowing, dry) and the intensity of flood and dry periods. A typical, long and short hydrological period was also defined in number of days based on the duration of each period. Considering that environmental abiotic and biotic modifications are related to water level fluctuation, the standardization of the hydrological nomenclature may become a useful tool for ecological data analysis.